Solid-state battery, solid-state electrolyte film and preparation method thereof

By low-temperature thermal modification, the solid electrolyte material is treated and mixed with oily dispersants and binders, a slurry that is easy to coat is formed, solving the problems of cumbersome preparation process and high energy consumption of existing oxide solid electrolytes, and achieving the safety and performance improvement of lithium-ion batteries.

CN119890424AInactive Publication Date: 2025-04-25JIANGXI JIULING LITHIUM CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411956603.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-29
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing oxide solid electrolytes are cumbersome in the industrial preparation process, have high energy consumption, and are difficult to prepare large-area and ultra-thin dense ceramic electrolytes, which affects the safety and performance of lithium-ion batteries.

Method used

By performing low-temperature thermal modification of organic weak acid and solid electrolyte material, the modified material is mixed with oily dispersant and binder to dissolve to form a slurry that is easy to coat, and a solid electrolyte film is prepared directly on the separator.

Benefits of technology

The preparation process is simplified, energy consumption is reduced, and uniform coating of solid electrolyte film is achieved, which improves the safety and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890424A_ABST
    Figure CN119890424A_ABST
Patent Text Reader

Abstract

The invention provides a solid-state battery, a solid-state electrolyte film and a preparation method thereof. The preparation method of the solid electrolyte film comprises the following steps: carrying out low-temperature thermal modification treatment on organic weak acid and a solid electrolyte material; mixing and dissolving the modified solid electrolyte material, an oily dispersant and a binder in an organic solvent according to a preset proportion to obtain slurry; and coating the slurry on a diaphragm, and drying and shaping to obtain the solid electrolyte film. By adding organic acid for modification, the stability of the powder in a solution is improved, the surface property of the powder is changed, the surface energy is reduced, and the agglomeration phenomenon among particles is reduced, so that the powder can be conveniently coated on a diaphragm. And long-time high-temperature sintering of ceramic powder and introduction of an inorganic ceramic coating into the lithium battery diaphragm in a traditional process are not needed, so that the energy consumption is reduced, and the manufacturing cost and the process difficulty are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a solid-state battery, a solid-state electrolyte film and a preparation method thereof. Background Art

[0002] With the widespread application of lithium-ion batteries in the fields of power batteries and energy storage, people have put forward higher requirements for the energy density and fast charge and discharge performance of lithium-ion batteries, which has brought with it increasing safety risks. All-solid-state lithium-ion batteries use non-flammable or non-flammable solid electrolytes to replace the flammable organic electrolytes in traditional batteries, which can effectively solve the safety problems of lithium-ion batteries and improve the battery's operating temperature range, cycle life and energy density.

[0003] Among them, oxide solid electrolytes have been widely studied for their high stability and excellent ionic conductivity. However, the current industrial preparation method for oxide solid electrolytes usually adopts a high-temperature sintering method, which is cumbersome and energy-intensive. In addition, due to the inherent characteristics of the oxide solid powder itself, it is difficult to prepare a large-area, ultra-thin, dense ceramic electrolyte. Therefore, coating solid electrolyte materials on lithium-ion battery separators is also one of the research directions. However, since the oily slurry made from oxide solid electrolyte materials cannot be evenly coated on the battery separator, inorganic ceramic coatings are usually introduced on the lithium-ion battery separator in the market, and the process is relatively cumbersome. Summary of the invention

[0004] The present application provides a solid-state battery, a solid-state electrolyte film and a preparation method thereof that are conducive to facilitating coating and simplifying the preparation process.

[0005] In a first aspect, an embodiment of the present application provides a method for preparing a solid electrolyte film, the method comprising:

[0006] Performing low temperature thermal modification treatment on organic weak acid and solid electrolyte material;

[0007] The modified solid electrolyte material, the oily dispersant and the binder are mixed and dissolved in an organic solvent according to a preset ratio to obtain a slurry;

[0008] The slurry is coated on the separator and dried to obtain a solid electrolyte film.

[0009] According to the first aspect, in a possible implementation manner, the mass ratio of the organic weak acid to the solid electrolyte material is 0.5% to 3.0%.

[0010] According to the first aspect, in a possible implementation method, in the step of subjecting the organic weak acid and the solid electrolyte material to low-temperature thermal modification treatment, the thermal modification treatment temperature is 200°C to 300°C; and / or, the treatment time at the thermal modification treatment temperature is 1h to 4h; and / or, the heating rate to the thermal modification treatment temperature is 2°C / min to 6°C / min.

[0011] According to the first aspect, in a possible implementation manner, the organic weak acid includes formic acid, acetic acid or citric acid.

[0012] According to the first aspect, in a possible implementation, the solid electrolyte material is lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide, and lithium lanthanum zirconium oxide with doped elements, and the doped elements include one or more of tantalum, gallium, niobium, aluminum, silicon or magnesium.

[0013] According to the first aspect, in a possible implementation, the oily dispersant includes one of diammonium citrate, polyethylene glycol, hexadecyl, trimethylammonium bromide, sodium dodecylbenzene sulfonate or polysorbate; and / or the solvent includes one or more of N-methylpyrrolidone, ethanol, triethyl phosphate, N,N-dimethylformamide, dimethylacetamide, and isopropanol.

[0014] According to the first aspect, in a possible implementation, the binder includes an oily organic binder such as PVDF, PVDF-HFP, PAN, etc.; and / or the diaphragm includes one or more of PP, PE, and PET.

[0015] According to the first aspect, in a possible implementation manner, the mass ratio of the modified solid electrolyte material in the solvent in the slurry is 75% to 95%.

[0016] According to the first aspect, in a possible implementation manner, the slurry coating thickness is 1 μm to 50 μm. The thickness of the diaphragm is 1 μm to 150 μm.

[0017] In a second aspect, an embodiment of the present application further provides a solid electrolyte film, which is prepared according to the method for preparing the solid electrolyte film described in the first aspect.

[0018] In a third aspect, an embodiment of the present application further provides a solid-state battery, wherein the solid-state battery further comprises the solid-state electrolyte film according to the second aspect.

[0019] The solid-state battery, solid electrolyte film and preparation method provided by the present application improve the stability of the powder in the solution by adding organic acid modification, change the surface properties of the powder, reduce the surface energy, and reduce the agglomeration phenomenon between particles, so as to facilitate coating on the diaphragm. It does not require the long-term high-temperature sintering of ceramic powders in traditional processes and the introduction of inorganic ceramic coatings into lithium battery diaphragms, which saves energy consumption and reduces manufacturing costs and process difficulties. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0021] Figure 1 is a schematic flow chart of a method for preparing a solid electrolyte film according to an embodiment;

[0022] Figure 2 is the XRD spectrum of the solid electrolyte LATP material after thermal modification treatment in the first embodiment;

[0023] Figure 3 This is a 0.1C rate cycle diagram of a full battery assembled with the LATP solid electrolyte film in the first embodiment. DETAILED DESCRIPTION

[0024] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0025] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0027] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0028] In a first aspect, the present application provides a method for preparing a solid electrolyte film, such as Figure 1 As shown, the method comprises the following steps:

[0029] Step S10, subjecting the organic weak acid and the solid electrolyte material to low-temperature thermal modification treatment;

[0030] One or more of formic acid, acetic acid or citric acid are selected. These organic weak acids have functional groups that can react chemically with the surface of the solid electrolyte material, thereby changing the structure and properties of the material surface.

[0031] Lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), lithium lanthanum titanium oxide (LLTO), lithium lanthanum zirconium oxide (LLZO), and lithium lanthanum zirconium oxide (LLZO) doped with tantalum, gallium, niobium, aluminum, silicon or magnesium are used as target materials. These materials are widely used in solid-state batteries due to their high ion conductivity and good chemical stability.

[0032] The mass ratio of the organic weak acid to the solid electrolyte material is 0.5% to 3.0%. This ratio ensures that the organic weak acid can fully contact and react with the solid electrolyte material, while preventing excessive organic weak acid from damaging the material structure.

[0033] The thermal modification treatment temperature is controlled between 200 and 300° C. This temperature range can ensure the smooth chemical reaction between the organic weak acid and the solid electrolyte material, and can also prevent the material from decomposing or sintering due to excessive temperature.

[0034] The treatment time at the thermal modification treatment temperature is 1 to 4 hours, and the length of the treatment time depends on the degree of modification required and the nature of the material.

[0035] The heating rate to the thermal modification treatment temperature is 2-6°C / min. This heating rate can ensure that the material does not undergo drastic physical and chemical changes during the heating process, thereby ensuring the stability and controllability of the modification process.

[0036] Before low-temperature thermal modification, the solid electrolyte material should be fully pretreated, such as grinding, screening, etc., to ensure its uniform particle size and clean surface.

[0037] Step S20, mixing and dissolving the modified solid electrolyte material, oily dispersant and binder in an organic solvent according to a preset ratio to obtain a slurry;

[0038] The surface properties of the solid electrolyte material that has been subjected to low-temperature thermal modification treatment are improved, which is conducive to dispersion and stability in the solvent.

[0039] One of diammonium citrate, polyethylene glycol, hexadecyltrimethylammonium bromide (CTAB), sodium dodecylbenzenesulfonate (SDBS) or polysorbate is selected as the oily dispersant. These dispersants can effectively reduce the surface tension of the solid electrolyte material in the solvent and promote its dispersion and stability.

[0040] One or more of N-methylpyrrolidone (NMP), ethanol, triethyl phosphate, N,N-dimethylformamide (DMF), dimethylacetamide (DMAC), isopropanol, etc. are selected as solvents. These solvents have good solubility and volatility, can dissolve solid electrolyte materials, dispersants and binders, and are easily volatilized and removed during subsequent coating and drying processes.

[0041] Select oily organic binders such as PVDF, PVDF-HFP, PAN, etc. These binders can form a good interface with the solid electrolyte material and improve the mechanical strength and electrochemical properties of the film.

[0042] The mass proportion of the modified solid electrolyte material in the solvent in the slurry is 75% to 95%. This ratio ensures a high content of solid electrolyte material in the slurry, which is conducive to the subsequent preparation of the solid electrolyte film with high ion conductivity and good electrochemical properties. When preparing the slurry, the mass and proportion of each component should be strictly controlled to ensure the uniformity and stability of the slurry.

[0043] Step S30: coating the slurry on the diaphragm and drying and shaping the slurry to obtain a solid electrolyte film.

[0044] One or more of PP (polypropylene), PE (polyethylene) or PET (polyethylene terephthalate) can be selected as the diaphragm material. These materials have good mechanical properties and chemical stability, and can meet the preparation requirements of solid electrolyte films. The thickness of the diaphragm should be controlled between 1μm and 150μm. A diaphragm that is too thin may not provide sufficient mechanical support, while a diaphragm that is too thick may increase the internal resistance and weight of the battery. Therefore, when selecting the thickness of the diaphragm, it is necessary to comprehensively consider the performance requirements and manufacturing costs of the battery.

[0045] The coating method can be a scraper method, spray method, dip coating method, etc. The specific method should be determined according to the properties of the slurry and the coating thickness requirements. During the coating process, it is necessary to ensure that the slurry can be evenly and continuously coated on the diaphragm to avoid defects such as missing coating and bubbles.

[0046] The coating thickness of the slurry should be controlled between 1 μm and 50 μm. This range can ensure that the film has sufficient ion conductivity and avoid the degradation of battery performance caused by too thick a film.

[0047] The drying process is to remove the solvent in the slurry so that the solid electrolyte material forms a stable film on the diaphragm. The selection of drying conditions should be determined according to the properties of the solvent and the requirements of the film. Generally, the drying temperature should be controlled within an appropriate range to avoid thermal decomposition or deformation of the film. At the same time, the drying time should also be long enough to ensure that the solvent can be completely volatilized.

[0048] During or after the drying process, the film may be subjected to a shaping treatment, which may further improve the mechanical strength and electrochemical properties of the film. The shaping treatment may include heat pressing, stretching, and the like.

[0049] In this embodiment, the stability of the powder in the solution is improved by adding organic acid modification, the surface properties of the powder are changed, the surface energy is reduced, and the agglomeration phenomenon between particles is reduced, so that it is easy to coat on the diaphragm. There is no need for long-term high-temperature sintering of ceramic powder in traditional processes and the introduction of inorganic ceramic coatings in lithium battery diaphragms, which saves energy consumption and reduces manufacturing costs and process difficulty.

[0050] In a first embodiment:

[0051] 240 g of lithium aluminum titanium phosphate (LATP) electrolyte powder was mixed with 4.8 g of acetic acid in a muffle furnace and fired at 300° C. for 3 h at a heating rate of 2° C. / min, and then naturally cooled to room temperature.

[0052] 25 g of PVDF binder, 240 g of thermally modified LATP electrolyte powder and 15 g of trimethylammonium bromide were added to 300 g of NMP solvent, and the mixture was mechanically stirred for 720 min to be fully mixed, thereby obtaining a solid electrolyte slurry.

[0053] The prepared solid electrolyte slurry is coated on a 9 μm thick PE porous diaphragm, the slurry coating thickness is 3 μm, and the solid electrolyte film can be obtained after the diaphragm is dried.

[0054] like Figure 2 As shown, Figure 2The XRD diffraction pattern of LATP powder after low-temperature thermal modification with organic weak acid, the horizontal axis is the diffraction angle, and the vertical axis is the diffraction intensity. The positions of the XRD peaks correspond to the standard spectrum of LATP one by one, and no impurity peaks appear, indicating that the crystal structure of the sample is uniform and there is no obvious impurity phase.

[0055] like Figure 3 As shown, Figure 3 This is the 0.1C rate cycle diagram of the full battery assembled with LATP solid electrolyte film. The horizontal axis is the number of cycles, the left vertical axis is the specific capacity, and the right vertical axis is the charge and discharge efficiency. The solid electrolyte film obtained by slurry coating of the modified LATP powder uses lithium iron phosphate as the positive electrode and graphite material as the negative electrode. The assembled C||LATP||LFP full battery is cycled at 0.1C rate. After 150 cycles, the specific capacity remains at 150mAh / g, and the charge and discharge efficiency is maintained at about 96%, verifying the good cycle performance of the modified solid electrolyte film assembled battery.

[0056] In the second embodiment:

[0057] 240 g of gallium-doped lithium lanthanum zirconium oxide (Ga-LLZO) electrolyte powder was mixed with 4.8 g of acetic acid and fired at 300° C. for 3 h in a muffle furnace at a heating rate of 2° C. / min, and then naturally cooled to room temperature.

[0058] 25 g of PVDF-HFP binder, 240 g of thermally modified Ga-LLZO electrolyte powder and 15 g of trimethylammonium bromide were added to 300 g of DMF solvent, and the mixture was mechanically stirred for 720 min to be fully mixed, thereby obtaining a solid electrolyte slurry.

[0059] The prepared solid electrolyte slurry is coated on a 9 μm thick PE porous diaphragm, the slurry coating thickness is 3 μm, and the solid electrolyte film can be obtained after the diaphragm is dried.

[0060] In the third embodiment:

[0061] 240 g of tantalum-doped lithium lanthanum zirconium oxide (Ta-LLZO) electrolyte powder was mixed with 4.8 g of acetic acid and calcined at 200° C. for 4 h in a muffle furnace at a heating rate of 2° C. / min, and then naturally cooled to room temperature.

[0062] 25 g of PVDF binder, 240 g of thermally modified Ta-LLZO electrolyte powder and 15 g of trimethylammonium bromide were added to 300 g of NMP solvent, and the mixture was mechanically stirred for 720 min to be fully mixed, thereby obtaining a solid electrolyte slurry.

[0063] The prepared solid electrolyte slurry is coated on a 9 μm thick PE porous diaphragm, the slurry coating thickness is 3 μm, and the solid electrolyte film can be obtained after the diaphragm is dried.

[0064] In the fourth embodiment:

[0065] 240 g of tantalum-doped lithium lanthanum zirconium oxide (Ta-LLZO) electrolyte powder was mixed with 4.8 g of acetic acid and calcined at 300 °C for 4 h in a muffle furnace at a heating rate of 2 °C / min, and then naturally cooled to room temperature.

[0066] 25 g of PAN binder, 240 g of thermally modified Ta-LLZO electrolyte powder and 15 g of diammonium citrate were added to 300 g of triethyl phosphate solvent, and mechanically stirred for 720 min to fully mix them, thereby obtaining a solid electrolyte slurry.

[0067] The prepared solid electrolyte slurry is coated on a 9 μm thick PE porous diaphragm, the slurry coating thickness is 3 μm, and the solid electrolyte film can be obtained after the diaphragm is dried.

[0068] In the fifth embodiment:

[0069] 240 g of gallium-doped lithium lanthanum zirconium oxide (Ga-LLZO) electrolyte powder was mixed with 4.8 g of acetic acid and fired at 300° C. for 3 h in a muffle furnace at a heating rate of 2° C. / min, and then naturally cooled to room temperature.

[0070] 25 g of PAN binder, 240 g of thermally modified Ga-LLZO electrolyte powder and 15 gkg of diammonium citrate were added to 300 g of triethyl phosphate solvent, and the mixture was mechanically stirred for 720 min to be fully mixed to obtain a solid electrolyte slurry.

[0071] The prepared solid electrolyte slurry is coated on a 9 μm thick PE porous diaphragm, the slurry coating thickness is 3 μm, and the solid electrolyte film can be obtained after the diaphragm is dried.

[0072] In the sixth embodiment:

[0073] 240 g of tantalum-doped lithium lanthanum zirconium oxide (Ta-LLZO) electrolyte powder was mixed with 4.8 g of acetic acid and fired at 300° C. for 3 h in a muffle furnace at a heating rate of 2° C. / min, and then naturally cooled to room temperature.

[0074] 25 g of PVDF binder, 240 g of thermally modified Ta-LLZO electrolyte powder and 15 g of trimethylammonium bromide were added to 300 g of NMP solvent, and the mixture was mechanically stirred for 720 min to be fully mixed, thereby obtaining a solid electrolyte slurry.

[0075] The prepared solid electrolyte slurry is coated on a 9 μm thick PE porous diaphragm, the slurry coating thickness is 3 μm, and the solid electrolyte film can be obtained after the diaphragm is dried.

[0076] In a second aspect, an embodiment of the present application further provides a solid electrolyte film, which is prepared according to the method for preparing the solid electrolyte film described in the first aspect.

[0077] In a third aspect, an embodiment of the present application further provides a solid-state battery, wherein the solid-state battery further comprises the solid-state electrolyte film according to the second aspect.

[0078] Thanks to the improvements in the preparation method of the solid electrolyte film in the above embodiments, the solid electrolyte film in the second embodiment and the solid-state battery in the third embodiment of the present invention have the same technical effects as the preparation method of the solid electrolyte film in the above embodiments, which will not be described in detail here.

[0079] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the method of the present invention, addition of auxiliary steps, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a solid electrolyte film, characterized in that: The method includes. Performing low temperature thermal modification treatment on organic weak acid and solid electrolyte material; The modified solid electrolyte material, the oily dispersant and the binder are mixed and dissolved in an organic solvent according to a preset ratio to obtain a slurry; The slurry is coated on the separator and dried to obtain a solid electrolyte film.

2. The method for preparing a solid electrolyte film according to claim 1, characterized in that: The mass ratio of the organic weak acid to the solid electrolyte material is 0.5% to 3.0%.

3. The method according to claim 1, characterized in that: In the step of subjecting the organic weak acid and the solid electrolyte material to low-temperature thermal modification, the thermal modification temperature is 200° C. to 300° C.; and / or, The treatment time at the thermal modification treatment temperature is 1 hour to 4 hours; and / or, The heating rate to the thermal modification treatment temperature is 2°C / min to 6°C / min.

4. The method for preparing a solid electrolyte film according to claim 1, characterized in that: The organic weak acid comprises formic acid, acetic acid or citric acid; and / or, The solid electrolyte material is lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium lanthanum titanium oxide, lithium lanthanum zirconium oxide and lithium lanthanum zirconium oxide with doping elements, and the doping elements include one or more of tantalum, gallium, niobium, aluminum, silicon or magnesium.

5. The method for preparing a solid electrolyte film according to claim 1, characterized in that: The oily dispersant includes one of diammonium citrate, polyalkylene glycol, hexadecyl, trimethylammonium bromide, sodium dodecylbenzene sulfonate or polysorbate; and / or, The solvent includes one or more of N-methylpyrrolidone, ethanol, triethyl phosphate, N,N-dimethylformamide, dimethylacetamide, and isopropanol.

6. The method for preparing a solid electrolyte film according to claim 1, characterized in that: The binder includes an oily organic binder such as PVDF, PVDF-HFP, PAN, etc.; and / or, The separator includes one or more of PP, PE and PET.

7. The method for preparing a solid electrolyte film according to claim 1, characterized in that: The mass proportion of the modified solid electrolyte material in the solvent in the slurry is 75% to 95%.

8. The method for preparing a solid electrolyte film according to claim 1, characterized in that: The slurry coating thickness is 1 μm to 50 μm. The thickness of the separator is 1 μm to 150 μm.

9. A solid electrolyte film, characterized in that: The solid electrolyte film is prepared by the method for preparing a solid electrolyte film according to any one of claims 1 to 8.

10. A solid-state battery, characterized in that: The solid-state battery comprises the solid-state electrolyte film according to claim 9 above.

Citation Information

Cited By

  • Lithium ion battery assembly and preparation process of coating modified solid electrolyte film of lithium ion battery assembly

    CN120657220A

  • Lithium ion battery assembly and preparation process of coating modified solid electrolyte thin film thereof

    CN120657220B